(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
"To systematize students’ knowledge and improve their ability to think logically by solving physics problems." In this work, the method of using the interactive method in solving physics problems in general secondary schools is shown. Problem solving is organized step-by-step, and at each step the activity of students individually and in groups is evaluated, and the total score is announced at the end of the lesson.